2013
DOI: 10.1002/2013jg002402
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty analysis of modeled carbon and water fluxes in a subtropical coniferous plantation

Abstract: [1] Estimating the exchanges of carbon and water between vegetation and the atmosphere requires process-based ecosystem models; however, uncertainty in model predictions is inevitable due to the uncertainties in model structure, model parameters, and driving variables. This paper proposes a methodological framework for analyzing prediction uncertainty of ecosystem models caused by parameters and applies it in Qianyanzhou subtropical coniferous plantation using the Simplified Photosynthesis and Evapotranspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Whereas the uncertainty of land surface model parameters has been subject to intensive investigations (e.g., Ren et al, 2013;Xiao et al, 2014), and several works are dedicated to reducing this uncertainty, for example by parameter estimation with data assimilation methods (e.g., Safta et al, 2015), the other sources of uncertainty are less studied. Earlier work has concluded that parameter uncertainty alone cannot explain observed deviations between measured and simulated NEE (e.g., Pridhoko et al, 2008;Wang et al, 2011), and the remaining deviations are often attributed to model structural errors.…”
mentioning
confidence: 99%
“…Whereas the uncertainty of land surface model parameters has been subject to intensive investigations (e.g., Ren et al, 2013;Xiao et al, 2014), and several works are dedicated to reducing this uncertainty, for example by parameter estimation with data assimilation methods (e.g., Safta et al, 2015), the other sources of uncertainty are less studied. Earlier work has concluded that parameter uncertainty alone cannot explain observed deviations between measured and simulated NEE (e.g., Pridhoko et al, 2008;Wang et al, 2011), and the remaining deviations are often attributed to model structural errors.…”
mentioning
confidence: 99%
“…However, E0, Rref and LUEmax led to the greatest uncertainties in the NEP, followed by LSTopt and a. LSTmin and LSTmax led to low uncertainties in the NEP prediction. In addition to the parameters, forcing variables and model structure also resulted in uncertainties in the model outputs [40]. Observation instruments contain stochastic error.…”
Section: Uncertainties Resulted From Model Parametersmentioning
confidence: 99%
“…1, and more detailed information of the parameter estimation procedure was described by Braswell et al (2005) and Ren et al (2013).…”
Section: Parameterization Of Sipnetmentioning
confidence: 99%